مقارنة بين استخدام الأدوات الجراحية التنظيرية التقليدية و جهاز Microdebrider في العلاج الجراحي لآفات الحنجرة غير الخبيثة - إبراهيم, مصطفى; العلوني, فايز; محمد, علي (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: Microdebrider as a new technology in management of benign laryngeal lesions is a powered rotatory dissection device with suction assistance. The aim of our study is to evaluate its advantages and benefits. Patients and methods : 60 patients with benign laryngeal lesions (42 males and 18 females) underwent endoscopic surgery, divided into two groups: Group 1 ( traditional surgical instruments were used ) , Group 2 ( microdebrider was used). Results were evaluated during surgery and a month later. Results : Duration of surgery is lower (t test < t score : a = 0.05) , and bleeding is less when using microdebrider (calculated z < z theory: a = 0.05). There is no significant difference between two groups in terms of edema, recurrent and improvement of voice after one month . But adhesions rate after a month of surgery is lower when using a microdebrider. Conclusions: Microdebrider is a safe and effective device in management of benign laryngeal lesions that saves time of surgery , reduces bleeding and decreases the following adhesions . المقدمة :إن microdebrider تقنية جديدة في علاج آفات الحنجرة السليمة و هو جهاز آلي لاستئصال الأنسجة مزود بممص مساعد , و الهدف من دراستنا تقييم ميزاته و الفوائد التي يقدمها . المواد و الطرائق : 60 مريضاً لديهم آفات حنجرية سليمة ( 42 ذكراً , 18 أنثى ) , خضعوا لجراحة الحنجرة التنظيرية , قُسِّموا إلى مجموعتين : الأولى ( استخدمت الأدوات الجراحية التنظيرية التقليدية ) و الثانية ( استخدم microdebrider ) , و تم تقييم النتائج خلال الجراحة و بعدها بشهر. النتائج : مدة العمل الجراحي أقل عند استخدام microdebrider ( t للاختبار > t الحرجة : a=0.05 ) , النزف أقل عند استخدام microdebrider ( z المحسوبة > z النظرية : a=0.05 ) , لا يوجد فارق هام إحصائياً بين المجموعتين من حيث الوذمة و النكس و نتائج تحسن الصوت بعد شهر من الجراحة , نسبة الالتصاقات بعد شهر من الجراحة أقل عند استخدام microdebrider . الاستنتاجات : إن microdebrider جهاز آمن و فعال في علاج آفات الحنجرة السليمة يوفر الوقت خلال الجراحة و يقلل النزف و ينقص الالتصاقات التالية للجراحة بالمقارنة مع الأدوات الجراحية التنظيرية التقليدية .